Innovative music learning in â€œProfil Pelajar Pancasilaâ€ development for students: an intervention study through world wall applications - Mantaaba Zukhruf Nabilunnuha; Sunarto Sunarto; Syahrul Syah Sinaga; Wahyu Lestari (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
The importance of art education in instilling the principles of Pancasila that should be taught to pupils has diminished since the era of technological transformation. Learning the names of the Pancasila principles through music is a powerful tool. However, pupils lose interest in the process when learning is still presented in the traditional fashion. Student's strengths in global variety, mutual cooperation, independence, critical reasoning, and creativity can be cultivated through this music-learning process and included in their Pancasila student profiles. As a result, changes in music education are necessary for the extras. The study's overarching objective was to explain how interventions based on the world wall application might help students build a Pancasila profile to better serve their communities. The art and culture instructor and the tenth-grade pupils at MAN 2 Kediri in the city of Kediri participated in this study. This research uses observation, interviews, and written records to acquire its data. Â The results of this study indicate that learning the art of music at schools in trumpet practice using the wordwall.net application can stimulate the profile of Pancasila students by cultivating an open way of thinking, mutual respect, mutual care and collaboration. This research is expected to be an innovative medium for teaching music learning so that students can get to know music in various ways